The EFEKTIVITAS METODE TIGA SATU TIGA KATEKESE DARING AKAR RUMPUT PADA MASA PANDEMI COVID-19 - Kanisius Dadi (Jurnal Pendidikan dan Kebudayaan Missio, 2021)
Covid-19 pandemic conditioned people to implement social distancing in each social activity. This condition impacted the process of catechesis. This research aims to analyze the effectiveness of three one three online catechesis processes in keeping the essence of catechesis during the Covid-19 pandemic situation in grass root level. The facilitator of catechesis performed planning, implementation, and evaluation of the online catechesis using gadgets and the internet. Since the early 1980s, faith dan spiritual developers used computers and the internet to promote faith and spiritual development. The catechesis facilitator implemented "three one three" online catechesis methods to respond to popular online catechesis through social media, such as YouTube, Instagram, Facebook, during the Covid-19 pandemic situation. Those examples show only one-way communication of faith (faith monologue), which does not represent the essence of catechesis. The researcher employed the qualitative method in this descriptive research and applied random sampling to nine families of the primary community of Curug Parish-Tangerang City. The result shows that the three stages and the thirteen steps of the online catechesis process effectively keep the essence of catechesis as a faith dialogue or two communication methods.